Application of positron emission tomography imaging to personalize esophagogastric cancer care. Issue 8 (22nd January 2019) - Mondaca, Sebastian; Janjigian, Yelena Y.
Abstract : Positron emission tomography can guide staging and perioperative therapies in patients with localized esophagogastric adenocarcinoma. Ongoing research is investigating the clinical usefulness of functional imaging with tumor‐specific radiolabeled molecules to optimize biomarker selection, diagnosis, and treatment.